Changes in structural composition of field margins and related landscape homogenization following EU accession of Poland - Andrzej Wuczyński; Krzysztof Kujawa; Remigiusz Pielech; Wojciech Grzesiak; Paweł Jarzembowski; Sylwia Wierzcholska; Zygmunt Dajdok (Scientific Reports)
Abstract Field margins have considerable ecological significance in farming landscapes, but are subject to constant changes resulting from natural processes and anthropogenic pressures. Understanding the balance of these processes is important from an ecological and conservation perspective. We measured 20 variables related to margin composition, woody vegetation and adjacent cropland fragmentation in 70 field margins in SW Poland in 2004 and 2006 (Poland’s accession to the EU), and then resurveyed in 2021 by using the same protocol. We aimed to examine changes in structural and functional properties of the margins and their response to anticipated agricultural intensification. Over 17 years all field margins still existed in the landscape but there was a significant reduction in margin width, increase of the tree layer, and depth of the ditches. No significant changes were found in the shrub layer nor species composition of woody plants. Cutting trees and shrubs were more visible along roads whereas succession along railways. The mosaic pattern of adjacent fields has clearly reduced due to land consolidation. Overall, despite strong alterations of individual plots, the network of field margins appeared relatively resistant to agriculture transformation. The negative environmental effects of EU accession were more evident in the fields. Our findings emphasize the necessity of preserving various types of field margins that can counterbalance to deterioration of farmland biodiversity.